The Conflict Between the Soekarnoism Support Agency and the Indonesian Communist Party in 1964 - Bima Saputra; Putut Wisnu Kurniawan (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2023)
This study aims to find out how the dynamics of the old order press, especially the conflict between the Soekarnoism Support Agency and the Indonesian Communist Party in 1964.  The method used in this study is the historical method by applying the following steps: (1) Heuristics, (2) Criticism, (3) Interpretation, and (4) Historiography.  The use of historical sources in this study in the form of documents, archives, newspapers, books and journals can be accounted for for their validity.  The result of this research is the dominance of the Indonesian Communist Party (PKI) in the national political constellation during the Guided Democracy period.  It was feared that President Soekarno's closeness to the PKI could influence Indonesian politics. Therefore, several journalists, including Sayuti Melik, established a journalistic organization called the Soekarnoism Support Agency with the aim of stemming the PKI in the national political arena. Through a series of articles written by Sayuti Melik entitled Learning to Understand Soekarnoism, BPS fought back against the PKI by publishing articles in all press offices of BPS members.